(untitled) (Sebha University Conference Proceedings, 2025)
Global dynamism has contributed and with the marketing of new concepts in the world, it has pushed educational institutions to keep pace with various measeures that serve sustainable development and that require the university to be environmentally friendly. The research aimed to interpret the green university philosophy as an effective approach in achieving sustainable development, by presenting the conceptual framework for sustainability in universities and identifyying the most important features of the green university, it also aims to reach the necessary requirements for the transformation of univerities into green universities, capable of competing and working to achieve sustainability today, green universities are a new model in education strategies, working to integrate environmental issues and sustainability into their curricule, using green techniques and technology in addition to practicing environmentally friendly activities to achieve his. We followed the descriptive and analytical approach, and we finally reched the need to shift the role of univerities towards community service, transforming them into green univerities that work to achieve sustainable development, and partner with the environment to better confront its problems.